Deliberative assemblies: a strategy for building community agreements - Durán Palacio, Nicolasa María; Díaz Alzate, Magda Victoria; Tabares Castrillón, Juan Carlos; Suárez Pulgarín, Lyda Marcela (Cuadernos de Trabajo Social, 2021)
This article presents the experience of deliberative community assemblies in the participative processes of the Picacho con Futuro community development corporation, involving public decision-making to resolve community problems. A narrative qualitative design involving in-depth interviews with corporation leaders was used to identify that in the underlying community organisation, the establishment of participative spaces for deliberation promotes other forms of power and collective action to resolve problems; these forms are more related to building agreements for the political transformation of the territory and reconstructing relationships of trust and solidarity.